2018
DOI: 10.1101/482497
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly efficient multiplex human T cell engineering without double-strand breaks using Cas9 base editors

Abstract: Chimeric antigen receptor engineered T cell (CAR-T) immunotherapy has shownefficacy against a subset of hematological malignancies 1,2 , yet its autologous nature and ineffectiveness against epithelial and solid cancers limit widespread application. To overcome these limitations, targeted nucleases have been used to disrupt checkpoint inhibitors and genes involved in alloreactivity 3-6 . However, the production of allogeneic, "off-the-shelf" T cells with enhanced function requires multiplex genome editing stra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…In their first in-human phase I clinical trial with CRISPR/Cas9-engineered TCR-transduced human T cells, Stadtmauer et al reported translocation frequencies of about 0.01% to 5% [ 47 ], which is in line with previous reports on translocation frequencies of Transcription activator-like effector nuclease (TALEN)- [ 84 , 85 ] and CRISPR-edited [ 86 ] T cells. Translocation frequencies are different for individual gRNA combinations [ 47 , 86 ] and can, therefore, be reduced through informed selection of specific gRNAs. In addition, Cas9 variants such as base editors that circumvent double-strand breaks were shown to decrease translocation events significantly [ 86 ].…”
Section: Technology Developmentsupporting
confidence: 65%
See 1 more Smart Citation
“…In their first in-human phase I clinical trial with CRISPR/Cas9-engineered TCR-transduced human T cells, Stadtmauer et al reported translocation frequencies of about 0.01% to 5% [ 47 ], which is in line with previous reports on translocation frequencies of Transcription activator-like effector nuclease (TALEN)- [ 84 , 85 ] and CRISPR-edited [ 86 ] T cells. Translocation frequencies are different for individual gRNA combinations [ 47 , 86 ] and can, therefore, be reduced through informed selection of specific gRNAs. In addition, Cas9 variants such as base editors that circumvent double-strand breaks were shown to decrease translocation events significantly [ 86 ].…”
Section: Technology Developmentsupporting
confidence: 65%
“…Translocation frequencies are different for individual gRNA combinations [ 47 , 86 ] and can, therefore, be reduced through informed selection of specific gRNAs. In addition, Cas9 variants such as base editors that circumvent double-strand breaks were shown to decrease translocation events significantly [ 86 ].…”
Section: Technology Developmentmentioning
confidence: 99%
“… 1 The use of programmable nucleases to generate double-stranded DNA breaks (DSBs) followed by homology-directed repair can introduce a wide variety of modifications but is inefficient in non-dividing cells, and is typically accompanied by an excess of unwanted insertions and deletions (indels), translocations, or other chromosomal rearrangements. 2 Base editing directly modifies target DNA bases in living cells and has become widely used to correct or install point mutations in organisms ranging from bacteria to human embryos. 3 Base editors use a catalytically impaired Cas9 to open a single-stranded DNA loop at a specified genomic site ( Fig.…”
mentioning
confidence: 99%
“…Genetically modified T cells have demonstrated clinical efficacy in some therapeutic applications 27 , and there is an increasing body of evidence suggesting that the therapeutic potential of adoptive T cell therapies may be significantly enhanced by disruption of multiple genes in the same cell to achieve desirable cellular phenotypes. 28,29 Approaches using nucleases to introduce indel mutations in target genes, thereby disrupting their expression in T cells 30,31 , are effective but simultaneous creation of multiple DSBs in a target cell can result in genomic rearrangements and toxicities with variable frequencies 32,33 . Because ABEs function by making single nucleotide genomic changes without creating DSBs, multiplexed base editing with ABE8 is an attractive approach for creating genetically modified T cells.…”
Section: Application Of Abe8s To Therapeutic Targets In Primary Humanmentioning
confidence: 99%